-1/3-g=1/3

Simple and best practice solution for -1/3-g=1/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/3-g=1/3 equation:



-1/3-g=1/3
We move all terms to the left:
-1/3-g-(1/3)=0
We add all the numbers together, and all the variables
-g-1/3-(+1/3)=0
We add all the numbers together, and all the variables
-1g-1/3-(+1/3)=0
We get rid of parentheses
-1g-1/3-1/3=0
We multiply all the terms by the denominator
-1g*3-1-1=0
We add all the numbers together, and all the variables
-1g*3-2=0
Wy multiply elements
-3g-2=0
We move all terms containing g to the left, all other terms to the right
-3g=2
g=2/-3
g=-2/3

See similar equations:

| -9f+5+1=9-10f | | p=p-11 | | -2w+10=2w-10 | | x3=-48 | | -10-2j=-4j+8+8j | | 3c+5=4c-1 | | 2(3k+5)=9k-3(k+4)-1 | | 5x+1+x-9=9x-80 | | -2-5b=-3b | | |x|=60 | | Y=3x-9x-27x | | 4x+34=1-6 | | Y=x2-225 | | 12x+3+7x-2=90 | | 7p/10+9=15 | | 2.5x=5x+3 | | 7r-15=2r+10 | | 11=7t/4 | | (2x-10)=-3 | | 50.50+4x=56.10 | | 3x-6=1x-18 | | 12-222x+34=180 | | 3+-1x=-4 | | (5-3n)=4 | | (2x)+58=180 | | (−11/6)+m=-2/9​ | | 3.5g+7=1.5g+15= | | -13=20m+5-2m | | 5x-1+15x+1=25x-25 | | 6.68=  2.3c+0.72.3c+0.7 | | -13=22m | | 3y+4=6y-+19 |

Equations solver categories